Aspek Hukum Paralegal Militer dalam Tugas Pokok Prajurit TNI AD Korps Hukum Militer - Lubis, Arief Fahmi; Prasetyo, Boedi; Purwanto, Haeru (Wajah Hukum, 2026)
The development of a military paralegal system within the Indonesian Army (TNI AD) is a strategic step to address the challenges of providing prompt and effective legal assistance, particularly in remote units or operational areas. Military paralegals, consisting of military personnel with basic legal training, have the potential to play a crucial role in supporting the duties of the Military Legal Corps (CHK), including providing legal assistance, managing legal administration, and providing legal education to soldiers. Although Law Number 16 of 2011 concerning Legal Aid and TNI Commander Regulation Number 46 of 2023 provide the legal basis for providing legal assistance, the absence of specific regulations regarding military paralegals in Indonesia creates gaps in the military legal system. Military paralegals play a role in supporting law enforcement, protecting soldiers' rights in accordance with the principle of due process of law, and strengthening the professionalism of the military legal system. Comparative studies with paralegal systems in other countries, such as the United States, demonstrate the need for structured education, certification, and strict oversight to ensure the efficiency and accountability of paralegals. Recommendations include the development of specific regulations, the development of a training curriculum, and the integration of paralegals into the CHK structure. With proper implementation, military paralegals can be a crucial element in strengthening justice and professionalism within the Indonesian military legal system.